Las Meniñas : Europees multimediaal project : Beijing 1994. - September Gallery, Beijing; Central Academy of Drama, Beijing; China Modern Art & Calligraphy Institute, Beijing (Kortrijk : Whitepuppettower p.v.b.a., 1994)
Aspoot, B. ; Betsens, Carlos M. ; Burton, Geoffrey ; Darge, Moniek ; De Smet, Pieter-Jan ; Huang Mei Cui ; Jorens, Piet ; Lambrecht, Mark ; Mysjkin, Jan H. ; Shen Rui ; Schauder, Silke ; etc.
Las Meniñas : Europees multimediaal project : Beijing 1994, September Gallery, Beijing / Central Academy of Drama, Beijing / China Modern Art & Calligraphy Institute, Beijing, 1994
boek